DONATION OF PROPERTY VERSUS ANNUITY – ANALYSIS OF VALIDITY OF APPLYING A SPECIFIC KIND OF CONTRACT IN FAMILY RELATIONS - Alicja MACIEJOWSKA (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2015)
The paper presents a comparative study of donation contract and annuity contract and their legal effects. Main emphasis is put on the time when a property owner takes a decision about entering into one form of legal construction or the other. The author of the paper discusses cases in which the donor’s expectations may, in the end, fail to overlap with the legal state defined by a given form of contract, which is often confirmed by life practice. The paper includes specific references to the position of the donor, annuitant and their contractors. The paper calls for a wider access to legal advice and relevant information for property owners who consider making a donation.